Process improvements for error-free sales reports from XYZ Sales Middle Office - Labrador, Javier Alfonso R. (Animo Repository, 2020)
Clients invest because they want to earn returns that are in line with their investment goals or objectives. Customers invest in XYZ Bank because they believe that we provide effective, efficient, and innovative solutions to best manage their financial needs. In this case, recording, reporting, and keeping of information is part of what customers expect when they purchase investments from XYZ Bank. Quality, then, is understood to be data accuracy. Accuracy means being free from errors or defects. My objective in doing this action paper was to achieve data accuracy by removing defects in the sales reports. Our end goal was to improve our process to produce error-free sales reports during primary bond offerings. To guide us removing defects in the Sales Reports, the concept of lean and six sigma methodologies were used. Lean defined the types of wastes to be removed, while six sigma provided the statistical tools and techniques. By using the concepts of lean and six sigma and by doing the action research cycles of constructing, planning, taking, and evaluating action, we were able to come up with process improvements for error-free sales reports.